Plus ça change" : los efectos de la región, número de asignaturas de ciencias cursadas y sexo sobre la opinión de los estudiantes canadienses en cuestiones de Ciencia, Técnica y Sociedad - Ryan, Alan G. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
An analysis of Canadian high school students' views on science -technology -society issues was undertaken in order to see if educationally significant differences in response were attributable to changes in three variables. The variables were: the region in which the students lived, the number of science courses being taken by the responding students, and the sex of the responder. On the whole, few variations among students' responses were found. The variations reported in the paper included the findings that Maritimer students tend to have a more idealistic view of how scientists conduct their work, that students who are taking three science courses have a greater understanding of the role of models in science, and that males, apart from a small group of male chauvinists, offer the same reasons as females to explain why there are fewer Canadian female scientists than males.